Photon management properties of rare-earth (Nd, Yb, Sm)-doped CeO2 films prepared by pulsed laser deposition. Issue 4 (24th December 2015) - Balestrieri, Matteo; Colis, Silviu; Gallart, Mathieu; Schmerber, Guy; Bazylewski, Paul; Chang, Gap Soo; Ziegler, Marc; Gilliot, Pierre; Slaoui, Abdelilah; Dinia, Aziz
Abstract : The luminescence of lanthanides in CeO2 films is sensitized by intrinsic Ce 3+ ions. Abstract : CeO2 is a promising material for applications in optoelectronics and photovoltaics due to its large band gap and values of the refractive index and lattice parameters, which are suitable for silicon-based devices. In this study, we show that trivalent Sm, Nd and Yb ions can be successfully inserted and optically activated in CeO2 films grown at a relatively low deposition temperature (400 °C), which is compatible with inorganic photovoltaics. CeO2 thin films can therefore be efficiently functionalized with photon-management properties by doping with trivalent rare earth (RE) ions. Structural and optical analyses provide details of the electronic level structure of the films and of their energy transfer mechanisms. In particular, we give evidence of the existence of an absorption band centered at 350 nm from which energy transfer to rare earth ions occurs. The transfer mechanisms can be completely explained only by considering the spontaneous migration of Ce 3+ ions in CeO2 at a short distance from the RE 3+ ions. The strong absorption cross section of the f–d transitions in Ce 3+ ions efficiently intercepts the UV photons of the solar spectrum and therefore strongly increases the potential of these layers as downshifters and downconverters.